An action research on the use of role play to enhance L2 learning of primary school students / Salim Sabang - Sabang, Salim (2004)
English is a very important language that has a lot of functions. Teaching English is a very challenging task for the English language teachers in Malaysia. Therefore, The Ministry of Education has been introducing new English Programmes from time to time to include new techniques in enhancing the teaching and learning of English in Malaysian schools. This study sought to introduce role play as a potential technique that can be used to enhance the process of teaching and learning the English language. This can be an addition to the existing methods and techniques that are being used. The study was conducted at Sekolah Kebangsaan Buntal, Kuching. 30 Year 4 students were used as the sample for the purpose of this study. 3 consecutive lessons incorporating role play was planned and conducted.